Using Transcriptome Analysis to Identify Genes Involved in Switchgrass Flower Reversion - Yongfeng, Wang; Aiquan, Zheng; Fengli, Sun; Mao, Li; Kaijie, Xu; Chao, Zhang; Shudong, Liu; Yajun, Xi (Frontiers in Plant Science, 2018)
Floral reversion is a process in which differentiated floral organs revert back to vegetative organs. Although this phenomenon has been described for decades, the underlying molecular mechanisms remain unclear. In this study, we found that immature switchgrass (Panicum virgatum) inflorescences can revert to neonatal shoots when incubated on a basal medium with benzylaminopurine. We used anatomical and histological methods to verify that these shoots were formed from floret primordia through flower reversion. To further explore the gene regulation of floral reversion in switchgrass, the transcriptome of reversed, unreversed, and uncultured immature inflorescences were analyzed and 517 genes were identified as participating in flower reversion. Annotation using non-redundant databases showed that these genes are involved in signal transduction, energy metabolism, and transcriptional regulation processes crucial for switchgrass flower reversion. When some of the genes were overexpressed in Arabidopsis thaliana, vegetative growth was facilitated and reproductive growth was inhibited in transgenic plants. This study provides a basic understanding of genes regulating the floral transition in switchgrass and will promote the research of floral reversion and flower maintenance.